2018
DOI: 10.1056/nejmoa1800024
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role ofBRCA2in Ovarian Development and Function

Abstract: The causes of ovarian dysgenesis remain incompletely understood. Two sisters with XX ovarian dysgenesis carried compound heterozygous truncating mutations in the BRCA2 gene that led to reduced BRCA2 protein levels and an impaired response to DNA damage, which resulted in chromosomal breakage and the failure of RAD51 to be recruited to double-stranded DNA breaks. The sisters also had microcephaly, and one sister was in long-term remission from leukemia, which had been diagnosed when she was 5 years old. Drosoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(57 citation statements)
references
References 28 publications
7
46
0
Order By: Relevance
“…Fertility defects are a common feature in FA gene knockout female mice, as well as in FA patients (Tsui & Crismani, 2019), which highlights the vital role of FA genes in germ cell development. Until now, besides FANCD1/BRCA2, FAMCM , and FANCU/XRCC2 (Fouquet et al, 2017; Qin et al, 2019; Weinberg‐Shukron et al, 2018; Zhang et al, 2019), novel potential causative mutations in the FANCL gene were also found in the present study. Considering that individuals with deficiency in FA genes are highly susceptible to multiple malignant tumors, such as breast and ovarian carcinoma, head and neck squamous cell carcinoma, and leukemia (Ceccaldi et al, 2016; Chandrasekharappa et al, 2017; Nalepa & Clapp, 2018), the long‐term surveillance of tumorigenesis is strongly suggested in patients with POI carrying FA gene mutations.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Fertility defects are a common feature in FA gene knockout female mice, as well as in FA patients (Tsui & Crismani, 2019), which highlights the vital role of FA genes in germ cell development. Until now, besides FANCD1/BRCA2, FAMCM , and FANCU/XRCC2 (Fouquet et al, 2017; Qin et al, 2019; Weinberg‐Shukron et al, 2018; Zhang et al, 2019), novel potential causative mutations in the FANCL gene were also found in the present study. Considering that individuals with deficiency in FA genes are highly susceptible to multiple malignant tumors, such as breast and ovarian carcinoma, head and neck squamous cell carcinoma, and leukemia (Ceccaldi et al, 2016; Chandrasekharappa et al, 2017; Nalepa & Clapp, 2018), the long‐term surveillance of tumorigenesis is strongly suggested in patients with POI carrying FA gene mutations.…”
Section: Discussionsupporting
confidence: 68%
“…Recently, mutations in three FA genes, including FANCD1/BRCA2 , FANCM , and FANCU/XRCC2 (Howlett et al, 2002; Shamseldin, Elfaki, & Alkuraya, 2012; Singh et al, 2009), have been identified in patients with POI (Fouquet et al, 2017; Qin, Zhang, & Chen, 2019; Weinberg‐Shukron et al, 2018; Zhang et al, 2019), thus suggesting the importance of the FA pathway in ovarian development and function. Ubiquitination of the FANCI‐D2 complex is a key event in this pathway, and thus failure of ubiquitination due to impaired function of FANCL will prevent the activation of the FA pathway (Wang & Smogorzewska, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…An allele that promotes clonal mosaicism through predisposition to chromosome missegregation or repair/generation of DNA damage would likely be associated with an earlier menopause due to acquired DNA damage in oocytes and their subsequent elimination. This principle is most evident in mice and humans with BRCA1/2 loss of function, where diminished double strand break repair in oocytes triggers apoptosis and depletion of the ovarian reserve 30,41,42 . In contrast, any process that impairs DNA damage sensing or programmed cell death may also promote clonal mosaicism (via greater tolerance of damaged cells) but lead to a later menopause.…”
Section: Discussionmentioning
confidence: 99%
“…However, BRCA2 deficient mice are able to produce competent and fertilised oocytes but more abnormal embryos are observed [146], indicating an important role of BRCA2 in the oocyte. In women, complete loss of BRCA2 function leads to ovarian dysgenesis resulting in primary amenorrhea, with reduced Rad51 function in HR indicated by low Rad51 expression at the site of DNA damage [147]. A genome-wide association study (GWAS) analysis also shows association between DNA damage repair and age at menopause [148], particularly highlighting links with BRCA1.…”
Section: Dna Damage Associated With Ovarian Ageing a Crosstalk Betwementioning
confidence: 99%
“…BRCA2 and Rad51 Lack of BRCA2 reduces Rad51 recruitment during homologous recombination. [147] Ovarian reserve in patients with BRCA1 mutation. Case-control study.…”
Section: Retrospective Cohort Study Brca1 and Brca2mentioning
confidence: 99%